Which is the better choice for open tibial shaft fracture in overweight adolescent with open physis: A comparative study of external fixator plus elastic stable intramedullary nail versus external fixator alone. Issue 10 (October 2021) - Hong, Pan; Rai, Saroj; Liu, Xiangyang; Tang, Xin; Liu, Ruikang; Li, Jin
Highlights: External Fixator (EF) is not the optimal choice for overweight teenagers with open tibial fracture. Application of plating in open fractures requires discretion. ESIN + EF provides an alternative for overweight kids with open tibial shaft fracture Abstract: Purpose: To compare the clinical outcomes of external fixator + elastic stable intramedullary nail (EF+ESIN) vs. external fixator (EF) in the treatment for open tibial shaft fracture in overweight adolescents. Methods: Patients of open tibial shaft fractures younger than 14 years old with body weight over 50 Kg treated with EF + ESIN or EF at our institute from 2010 to 2018 were reviewed. Patients with Gustilo Type III open fractures, pathological fractures, previous fracture or instrumentation in the operative leg were excluded. Baseline information and clinical data were collected from the hospital database and during out-patient visits. Results: Forty-six patients, including 27 males and 19 females, were included in the EF group, whereas 35 patients, including 18 males and 17 females, were included in the EF + ESIN group ( p = 0.527). The incidence of superficial infection was higher in the EF group (26/46, 56.5%) than the EF + ESIN group (12/35, 34.3%), p < 0.001. The frontal and sagittal angulation was higher in the EF group ( p < 0.001), but the degrees in both groups were within the acceptable range. The union time was longer in the EF group (68.0 ± 12.7, d) than the EF + ESIN group (61.9 ± 11.9), p < 0.001. The retaining of EF (11.9 ± 3.2, w) was longer in the EF group than the EF +ESIN group (5.7 ± 1.2, w), p < 0.001. Conclusion: EF+ESIN is a safe and alternative choice for selected overweight adolescents with open tibial shaft fracture.